A bilingual child's language profile: Impaired English but intact Vietnamese. (1st September 2013) - Hemsley, Gayle; Holm, Alison; Dodd, Barbara
Abstract : The literature asserts that language impairment always manifests in both languages of a bilingual child. The case reported describes a boy, aged 8 years whose first language (L1, Vietnamese) is intact while his acquisition of English (L2, learned from 4 years) is significantly impaired. Culturally appropriate language assessments included dynamic assessment, composite scoring, and peer-child comparison. Analysis revealed poor L2 lexical development, with underspecified lexical templates and inhibited access to lexical knowledge in English. No such difficulties were evident in L1. Peter's profile allows evaluation of current models of bilingual language development. A specific deficit in lexical inhibition of L1 might plausibly account for impairment only in L2.